Studi Komparatif Implementasi Pendidikan Fikih Melalui Praktik Berbuka Puasa Ramadan Pada Tpa Darussalam Sukoharjo Dan Tpa Al-Hidayah Boyolali - Mumtazah, Muti’ah Nuha; Aisha Inda Nursifa; Ma'shum, Qodim (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2026)
This Study aims analyze comparatively the implementation of fiqh education through the practice of breaking the fast during Ramadan at TPA Darussalam Sukoharjo and TPA Al-Hidayah Boyolali. The background of this research is the importance of integrating theoretical understanding with practical worship in fiqh education within non-formal educational institutions. The study employs a qualitative approach with a descriptive-comparative design. Data were collected through observation and interviews with TPA leaders, teachers (ustaz/ustazah), and students involved in Ramadan activities. The results show that TPA Darussalam applies a systematic and structured approach, characterized by regular iftar practices, habituation of collective prayers, and evaluation of attitudes and understanding. Meanwhile, TPA Al-Hidayah adopts a more flexible and dialogical approach, emphasizing the understanding of the meaning of fasting; however, the practices have not been implemented consistently. The main differences lie in aspects of planning, consistency of practice, and evaluation systems. This study concludes that the integration of structured practical habituation and dialogical deepening of meaning constitutes an ideal model for implementing fiqh education based on the practice of breaking the fast during Ramadan in TPA.